Classification of ion-beam-induced traits in Thai jasmine rice mutants using synchrotron radiation FTIR microspectroscopy - E. Kongmon (2020)
© 2019 Elsevier B.V. Thai jasmine rice is one of the prominent agricultural products of Thailand. Although it has made high export value for the country, the annual crop yield is limited by its photoperiod sensitivity and low disease resistance. Aiming to improve the rice traits, ion beam-induced genetic modification technique had been applied to the original jasmine rice, resulting in five selected agriculturally stable mutants. To overcome the complexity of conventional chemical test, we utilise the synchrotron-radiation-based FTIR microspectroscopy to investigate the main biochemical contents of rice samples. The infrared spectra were analysed to extract information on interesting components, including relative content quantification. Classification of rice traits based on spectroscopic data was performed by using principal component analysis (PCA). The PCA analysis results of the measured spectra in the carbohydrate region suggest that the mutant rice traits HyKOS3 and HyKOS3-1 are well separated from the original KDML105 rice. In contrast, the mutant rice traits HyKOS21 and HyKOS22 are seem to be inseparable from the original trait. The peak ratio of the crystallinity (1047 cm-1/1022 cm-1) for HyKOS21 shows significantly higher degree of order in the starch granule than the KDML105 rice. The results clearly demonstrate the differences and similarities between rice cultivars, showing the interest of using this technique as a preliminary examination for genetically modified biological samples.